'Persistent Centrism' and Its Explanations. (December 2016) - Singh, Ujjwal Kumar; Roy, Anupama
Susanne Rudolph and Lloyd Rudolph believed that 'situated knowledge' could be realized through area studies, which they argued was consonant with epistemic pluralism and comparative generalization. Their writings reflect a critical relationship with their field as well as the American Political Science academia particularly in the way they envisaged area studies of 'a different kind'. The Rudolphs proposed that the Indian state and political process could be comprehended through analytical categories 'adapted' to capture its particularity. They found 'a persistent centrism' to be the most striking feature of Indian politics with the Indian National Congress crucial to the arrival at 'centrism'. In their later writings, the Rudolphs addressed the contests that emerged in the domain of the state, particularly in the context of the diminished 'interventionist state', grappling with contests over political power, the institutional matrix of the state and constitutional design.